Enhancing the performance of self-powered ultraviolet photosensor using rapid aqueous chemical-grown aluminum-doped titanium oxide nanorod arrays as electron transport layer - Mohd Yusoff, Marmeezee; Mamat, M. H.; Ismail, Ahmad Syakirin; Malek, Mohd Firdaus; Khusaimi, Zuraida; Abu Bakar, Suriani; Mohamed, Azmi; Ahmad, Mohd Khairul (Elsevier, 2018)
Aluminum (Al)-doped titanium dioxide nanorod arrays (ATNs) were grown on fluorine-doped tin oxide-coated glass at different Al atomic concentrations ranging from 1 at.% to 5 at.% in a Schott bottle through single-step aqueous chemical growth for self-powered photoelectrochemical cell-type ultraviolet (UV) photosensor applications. X-ray diffraction patterns showed that the grown ATNs exhibited a crystalline rutile structure. The ATNs showed smaller crystallite size and average nanorod diameter and length compared with the undoped sample. The photocurrent measured from the fabricated UV photosensors improved to some extent with increasing Al-dopant concentration. Samples with 2 at.% Al showed the maximum photocurrent of 108.87 μA/cm2 at 0 V bias under UV irradiation (365 nm, 750 μW/cm2). The results show that high-performance UV photosensors can be fabricated and enhanced using ATNs easily prepared in a glass container.